ADDRESSING CLIMATE CHANGE THROUGH ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) INITIATIVES: A PRAGMATIC OUTLOOK IN PRESENT ERA - Adhana, Deepak Kumar; Rashmi, (International Journal of Research -GRANTHAALAYAH, 2023)
The research explores the pivotal role of Environmental, Social, and Governance (ESG) initiatives in addressing the pressing issue of climate change. As global awareness of environmental challenges grows, businesses, investors, and policymakers increasingly recognize the significance of integrating ESG principles into their strategies. This paper examines how ESG initiatives contribute to mitigating climate change through a holistic approach that encompasses environmental stewardship, social responsibility, and effective corporate governance. This study investigates climate change mitigation through Environmental, Social, and Governance (ESG) initiatives in the context of Small and Medium-sized Enterprises (SMEs) in Rajasthan, India. With a sample size of 370 SMEs, the research employs the Smart-PLS software for comprehensive analysis. Our study explores the pragmatic role of ESG practices in addressing climate change challenges SMEs face in the present era. The findings underscore the significance of integrating sustainability strategies to ensure environmental resilience, social responsibility, and effective governance. While offering valuable insights, the study acknowledges limitations in the scope of ESG factors and the evolving nature of climate change dynamics. Ultimately, the study underscores the importance of collective efforts among stakeholders to foster sustainable practices and combat climate change impacts in Rajasthan's SME sector.